Mapping Oat Crown Rust Resistance Gene Pc45 Confirms Association with PcKM. Issue 2 (1st February 2019) - Kebede, Aida Z; Friesen-Enns, Jayelle; Gnanesh, Belaghihalli N; Menzies, Jim G; Mitchell Fetch, Jennifer W; Chong, James; Beattie, Aaron D; Paczos-Grzęda, Edyta; McCartney, Curt A
Abstract: Molecular mapping of crown rust resistance genes is important to effectively utilize these genes and improve breeding efficiency through marker-assisted selection. Pc45 is a major race-specific crown rust resistance gene initially identified in the wild hexaploid oat Avena sterilis in the early 1970s. This gene was transferred to cultivated oat ( Avena sativa ) and has been used as a differential for identification of crown rust races since 1974. Previous research identified an association between virulence to Pc45 and PcKM, a crown rust resistance gene in the varieties 'Kame' and 'Morton'. This study was undertaken to reveal the relationship between Pc45 and PcKM . Pc45 was studied in the crosses 'AC Morgan'/ Pc45 and 'Kasztan'/ Pc45, where Pc45 is the differential line carrying Pc45 . F2 progenies and F2:3 families of both populations were inoculated with the crown rust isolate CR258 (race NTGG) and single gene segregation ratios were observed. SNP markers for PcKM were tested on these populations and linkage maps were generated. In addition, 17 newly developed SNP markers identified from genotyping-by-sequencing (GBS) data were mapped in these two populations, plus another three populations segregating for Pc45 or PcKM . Pc45 and PcKM mapped to the same location of Mrg08 (chromosome 12D) of the oat chromosome-anchored consensus map. These results strongly suggest that Pc45 and PcKM are the same resistance gene, but allelism ( i.e., functionally different alleles of the same gene) or tight linkage ( i.e., two tightly linked genes) cannot be ruled out based on the present data.